Attitudes and Behavior of Occupational Health and Safety in Mina MSME - Hardani Widhiastuti; Mulya Virgonita IW; Rusmalia Dewi; Rosalia T Gabronino; Rebecca Maquilling (Fakultas of Psychology, Universitas Muria Kudus, 2025)
This research was conducted in order to participate in resolving the problem of Occupational Health and Safety (OHS) Attitudes and Behavior, which occurred in Micro, Small, and Medium Enterprises (MSME) Processed Mina in Banjarsari village, Sayung coastal area, Central Java. Many fish processing businesses in the area only pursue profits to help the household economy, considering that their business productivity has not developed/increased, which is likely due to a lack of attention to conscious efforts to carry out or comply with Occupational Health and Safety, such as using personal protective equipment such as gloves, boots, or in processing fish related to stoves, there are no manual extinguishers for home businesses. This research is a population study with 38 respondents who are average fish processors and fishermen. The research method is quantitative with SPSS statistical analysis obtained results that the Attitude variable has a t value = 7.685 with Sig. = 0.000 (<0.05), indicating that Attitude has a positive and significant effect on Behavior (OHS). The regression coefficient value of 0.824 indicates that every one-unit increase in OHS Attitude will increase OHS Behavior by 0.824 units. Thus, it can be concluded that the more positive a person's attitude toward OHS implementation, the better their OHS behavior.